Chapter I: Graphic Analysis: Simplest Case (Quarterly Journal of Economics, 1938)
Journal Article Chapter I: Graphic Analysis: Simplest Case Get access The Quarterly Journal of Economics, Volume 52, Issue Supplement, May 1938, Pages 9–26, https://doi.org/10.1093/qje/52.Supplement.9 Published: 01 May 1938